(untitled) (Journal of Educational Management, 2000)
Many mathematics teachers in Ghanaian secondary schools have little or no training in the teaching of mathematics, yet they teach the subject because of the shortage of mathematics teachers in Ghana. Such teachers and their trained counterparts, need professional help to enable them guide pupils learn the subject effectively and efficiently especially since the duration for pre-university education in Ghana has been cut by about five. This study aimed to; 1. Examine the nature of teacher appraisal in Ghana . 2. Examine the validity of existing methods of teacher appraisal in Ghana. 3. Determine which variables influence Ghanaian mathematics teachers’ views about teacher appraisal and its ability to help them improve their competence of teaching mathematics. Of the 441 secondary mathematics teachers who participated in the study, 193 taught the subject at the junior secondary level and 248 taught it at the senior secondary level. In addition, 44 Ghana Education Service Officials and six heads of secondary schools who appraise mathematics teachers were sampled. Methods used included questionnaires, interviews and observation of appraisers at work. Highly significant relationships were found between mathematics teachers’ perceived professional support and appraisal experience, mathematics teaching experience and professional status at the senior secondary level, and between received support and appraisal experience at the junior secondary level. The results indicated a dramatic difference between junior secondary and senior secondary mathematics teachers in their perception of the potential of the teacher appraisal system in Ghana to help them to improve their teaching of mathematics. Senior secondary mathematics teachers were generally more pessimistic about the potential of the appraisal system than their junior secondary counterparts. The study also showed that many education officials who appraise mathematics teachers have little or no training in secondary school mathematics teaching or its appraisal, yet the appraisal system for both formative and summative purposes require these officers to both "help " mathematics teachers improve their work and make judgements about their performance. These findings led to the conclusion that the teacher appraisal system in the Ghana Education Service is not valid. The implications of the findings are discussed.